2011
DOI: 10.5271/sjweh.3263
|View full text |Cite
|
Sign up to set email alerts
|

Tossing and turning – insomnia in relation to occupational stress, rumination, fatigue, and well-being

Abstract: Kompier MAJ, Taris TW, van Veldhoven M. Tossing and turning -insomnia in relation to occupational stress, rumination, fatigue, and well-being. Scand J Work Environ Health. 2012;38(3):238-246. doi:10.5271/sjweh.3263 Objectives This study of a large and heterogeneous sample of 5210 daytime employees was designed to shed more light on the work effort-recovery mechanism by examining the cross-sectional relations between subjective sleep quality and (i) psychosocial work characteristics, (ii) work-related rumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
63
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 33 publications
5
63
0
2
Order By: Relevance
“…As such, it is essential to determine the main causes of poor sleep quality as to reduce them and restore good sleep quality. Based on occupational health theories, workrelated stress and adverse psychosocial work characteristics are assumed to be important determinants of poor sleep quality (16,19,57). In 2006, a narrative review of mainly cross-sectional studies indeed showed that psychosocial work-related stress is closely related to impaired sleep quality (15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As such, it is essential to determine the main causes of poor sleep quality as to reduce them and restore good sleep quality. Based on occupational health theories, workrelated stress and adverse psychosocial work characteristics are assumed to be important determinants of poor sleep quality (16,19,57). In 2006, a narrative review of mainly cross-sectional studies indeed showed that psychosocial work-related stress is closely related to impaired sleep quality (15).…”
Section: Discussionmentioning
confidence: 99%
“…Poor sleep quality could lead to fatigue and also to poor work functioning and decreases in performance. Poor work performance, in turn, may also "create" work stressors, such as reduced support from colleagues or supervisors or insecurity (19). This is what De Lange et al (28) define as the "environmental change mechanism".…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep quality is an important clinical construct in maintaining health. Poor sleep quality which results from many sleep disorders as well as medical diseases, might even have a direct effect on increased mortality [5]. Sleep loss is a common condition in new lifestyle while in many instances, its potential adverse impact is under-attended [6].…”
Section: Introductionmentioning
confidence: 99%